THE USE OF GAMES AND INTERACTIVE ACTIVITIES IN GRAMMAR INSTRUCTION - Aziza Xujaqulova Uzbekistan State World Language University The Second English Faculty 2nd-year student., (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Grammar, often viewed as the backbone of language proficiency, has traditionally been taught through mechanical drills and rule memorisation, leading to student disengagement and anxiety. This article explores a more engaging554 and effective approach: the integration of games and interactive activities into grammar instruction. Drawing on both theoretical foundations and real classroom practice, it demonstrates how such activities can reduce learner anxiety, promote active participation, enhance motivation, and support the natural acquisition of grammatical structures. The paper presents a range of game types and interactive strategies suitable for different learning contexts and discusses how they can transform grammar from a dry subject into a dynamic and communicative experience. Real-world examples and academic studies are used to validate the effectiveness of these methods, offering practical guidance to educators seeking to innovate in their teaching practice.